Sum rate maximization in multi-operator two-way relay networks with a MIMO AF relay via POTDC - Jianshu Zhang; Vorobyov, Sergiy A.; Khabbazibasmenj, Arash; Haardt, Martin (21st European Signal Processing Conference (EUSIPCO 2013), 2013)
We address the beamforming problem for maximizing the sum rate of a multi-operator two-way relay (TWR) network subject to the constraint on the total relay transmit power. This scenario is also known as relay sharing for multi-way relaying or TWR for multiple operators. The relay is assumed to be equipped with multiple antennas, and it uses the amplify-and-forward relaying strategy. It is shown that the corresponding optimization problem can be represented as a difference of convex functions (DC) programming problem which is NP-hard in general. Nevertheless, we develop an efficient polynomial time algorithm to solve the problem approximately. The performance comparison of the proposed polynomial time DC (POTDC) inspired algorithm to the existing state-of-the-art algorithms demonstrate that the proposed algorithm outperforms the existing algorithms especially in the case of non-symmetric networks.